Description of Weak Halogen Bonding Using Various Levels of Symmetry-Adapted Perturbation Theory Combined with Effective Core Potentials - Piotr Matczak (Journal of Chemistry)
The present work starts with providing a description of the halogen bonding (XB) interaction between the halogen atom of MH3X (where M = C–Pb and X = I, At) and the N atom of HCN. This interaction leads to the formation of stable yet very weakly bound MH3X⋯NCH complexes for which the interaction energy (Eint) between MH3X and HCN is calculated using various symmetry-adapted perturbation theory (SAPT) methods combined with the def2-QZVPP basis set and midbond functions. This basis set assigns effective core potentials (ECPs) not only to the I or At atom directly participating in the XB interaction with HCN but also to the M atom when substituted with Sn or Pb. Twelve SAPT methods (or levels) are taken into consideration. According to the SAPT analysis of Eint, the XB interaction in the complexes shows mixed electrostatic-dispersion nature. Next, the accuracy of SAPT Eint is evaluated by comparing with CCSD(T) reference data. This comparison reveals that high-order SAPT2+(3) method and the much less computationally demanding SAPT(DFT) method perform very well in describing Eint of the complexes. However, the accuracy of these methods decreases dramatically if they are combined with the so-called Hartree-Fock correction.